Editorial :1.NLRP3 INFLAMMASOME: A PROMISING THERANOSTIC TARGET IN INFLAMMATORY DISEASES (Iraqi Journal of Medical Sciences, 2018)
Currently, the evaluation and treatment of chronic inflammatory diseases relies on specific clinical signs accompanied with single or multiple marker(s) for that disease. Despite that, these diseases share a common innate immune mechanism involved upregulation of “Inflammasome” that have been proved in its implication in the pathologic mechanism (s) and direct irreversible conversion of pro-interleukin 1? and pro-interleukin 18 into active IL-1b and active IL-18 contributing in disease progression and tissue damage, suggesting a common theranostic target to reduce inflammatory mechanism.Keywords: NLRP3, inflammasome, theranostic markerCitation: Ghazi HF. NLRP3 Inflammasome: a promising theranostic target in inflammatory diseases. Iraqi JMS. 2018; Vol. 16(1): 1-3. doi: 10.22578/IJMS.16.1.1
Keywords: NLRP3; inflammasome; theranostic marker